Drop Calorimetric Measurement of In-Zn system for Lead-Free solder applications - Singh V.; Jaiswal D.; Pathote D.; Behera C.K. (My University, 2025)
Circuit boards installed inside vehicles in the automotive industry are subjected to significant thermal stress due to temperatures above 150 °C. It can be reduced by using In-Zn solder alloys instead of hazardous Pb-based solder alloys, representing Pb-free solder alloys' development. The formation of an alloy is determined by its phase diagram, which is then measured to determine its thermodynamic properties. Using a drop calorimeter, the mixing heat effect (mixing enthalpy) as partial enthalpies and integral enthalpies of mixing in the liquid phase of In-Zn systems were investigated at 800 K and 900 K. The plots of mixing enthalpies are plotted versus zinc composition. When the Redlich–Kister polynomial is fitted, it is compared to our experimental data to identify the binary interaction parameters. This will help to predict the thermodynamic properties of multicomponent systems by using values of interaction parameters of the binary system (In-Zn). For all compositions at 800 K and 900 K, the model value was found to be close to the experimental values. The integral enthalpy of mixing of In-Zn system at 800 K and 900 K is endothermic in nature all through the composition and its most value in the range of XZn ∼ 0.48–0.52. It is also visible that the enthalpy of mixing is symmetrical with the composition of Zn. © 2022